2018
DOI: 10.1186/s12864-017-4419-6
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA-binding protein family members in laticifers are possibly involved in lipid and latex metabolism of Hevea brasiliensis (the Para rubber tree)

Abstract: BackgroundAcyl-CoA-binding proteins (ACBPs) are mainly involved in acyl-CoA ester binding and trafficking in eukaryotic cells, and their various functions have been characterized in model plants, such as Arabidopsis thaliana (A. thaliana), Oryza sativa (rice), and other plant species. In the present study, genome-wide mining and expression analysis of ACBP genes was performed on Hevea brasiliensis (the para rubber tree), the most important latex-producing crop in the world.ResultsSix members of the H. brasilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The results showed that bark tapping and JA stimulation increased the expression levels of HbACBP1 and HbACBP2, whereas ET only increased the expression level of HbACBP1 [10]. ET and bark tapping can promote the production of latex [27,28], and JA stimulation can promote laticifer differentiation [29], indicating that HbACBP1 and HbACBP2 play important roles in latex formation and lipid metabolism [10]. Therefore, as an important commercial resource, it is of great significance to explore the role of ACBP family proteins during the formation of latex.…”
Section: Acbp Family Proteins Can Promote Latex Formationmentioning
confidence: 95%
See 4 more Smart Citations
“…The results showed that bark tapping and JA stimulation increased the expression levels of HbACBP1 and HbACBP2, whereas ET only increased the expression level of HbACBP1 [10]. ET and bark tapping can promote the production of latex [27,28], and JA stimulation can promote laticifer differentiation [29], indicating that HbACBP1 and HbACBP2 play important roles in latex formation and lipid metabolism [10]. Therefore, as an important commercial resource, it is of great significance to explore the role of ACBP family proteins during the formation of latex.…”
Section: Acbp Family Proteins Can Promote Latex Formationmentioning
confidence: 95%
“…The third class is a large molecular weight ACBP that has a single ACBP domain, which is usually composed of 215-700 amino acids. The fourth category is the kelch motif ACBP, which typically consists of 648 to 668 amino acids and contains a kelch domain at the C-terminus along with the ACBP domain [10,20]. In addition to the kelch domain and the ANK domain, ACBP family proteins in humans and mammals also contain different numbers of the ECH domain, GOLD domain, and Herpes DNAp domain [15].…”
Section: General Characteristics Of Acbp Structure and Functionmentioning
confidence: 99%
See 3 more Smart Citations